The Quality of Life in Prisons: Do Educational Programs Reduce In-prison Conflicts? - María Laura Alzúa; Catherine Rodriguez; Edgar Villa (Universidad Nacional de La Plata, Centro de Estudios Distributivos, Laborales y Sociales (CEDLAS), 2009)
The harshness of punishment society chooses to impose on crime offenders is mandated by law. However, the quality of life in prison can make this punishment harsher. This creates a variation in the severity of punishment which is not legislated and may differ from society's taste for penalties. Indicators of in prison violence and conflicts seem to be appropriate proxy variables for prison conditions. Using indicators of in prison violent behavior, we use an exogenous source in education participation in educational programs in order to asses the effect of education on such measures of conflict. Applying instrumental variables techniques to census data for Argentine prisons, we find that educational programs significantly reduce indicators of property damages in prison. Such reductions amounts to a 60 percent decrease relative to the mean level of property damages.
Keywords: 330; Quality of life; prison; conflict; educational programs; education; Strafvollzug; Bildung; Lebensqualität; Sozialer Konflikt; Argentinien